Extremely high HIV-1 viral load in a patient with undiagnosed clinical indicator disease for HIV infection. (24th November 2015) - Flanagan, Stuart; De Saram, Sophia; Dhairyawan, Rageshri
Abstract : We report a case of a new diagnosis of HIV with an extremely high viral load presenting with HIV encephalopathy, in a 54-year-old woman who had been treated with 2 years of extended high-dose immunosuppressant therapy for a recalcitrant pruritic rash before diagnosis.